AM fungi mediated bioaccumulation of hexavalent chromium in Brachiaria mutica-a mycorrhizal phytoremediation approach. (November 2020) - Kullu, Bandana; Patra, Deepak Kumar; Acharya, Srinivas; Pradhan, Chinmay; Patra, Hemanta Kumar
Abstract: The experiment was designed to evaluate the roles of Rhizophagus irregularis on chlorophyll fluorescence and chromium bioaccumulation in a grass species ( Brachiaria mutica ) by supplementing Cr +6  at different concentrations. Arbuscular Mycorrhizal Fungi (AMF) association facilitated lessening of chromium level in contaminated soil and enhanced chromium bioavailability in Brachiaria mutica . The mycorrhizal inoculated increased the chlorophyll (0.925 mg/g), carotenoid (0.127 mg/g), protein (2.883 mg/g), proline (0.889 mg/g) contents and activities of antioxidant enzymes like catalase, ascorbate peroxidase and glutathione peroxidase. The mycorrhizal inoculated plants also showed enhanced overall photosynthetic performance (PIϕ  = 2.473) and enhanced PS–II to PS–I electron transport as evident from yield parameter (0.712) and TR0 /RC (2.419) for 60 mg/kg Cr +6 treatment. The observations suggest that AMF association could defend the plants from chromium stress by elevating the number of antioxidants in plants. Rhizophagus irregularis was found to maintain a successful symbiotic relationship with Brachiaria mutica in chromium contaminated soil. The observations recommended that Rhizophagus irregularis in association with Brachiaria mutica would be an innovative approach for decontamination of Cr +6 . Graphical abstract: Image 1 Highlights: Arbuscular Mycorrhizal Fungi (AMF) induced phytoremediation efficiency and tolerance capacity of Brachiaria mutica to hexavalent chromium (Cr +6 ) toxicity. AMF association possibly defends the plants from oxidative stress induced by hexavalent chromium by altering the metabolic processes of the plant. AMF enhanced the tolerance index, bioconcentration factor and transportation index of Brachiaria mutica. AM fungi enhanced the photosynthetic performance and quantum yield in B. mutica under Cr +6 stress.